Impact of pregnancy and childbirth on the urinary tract - Távara, Luis (2015)
The association between genital and urinary organs has been established for many years. Kahum papyrus, written in ancient Egypt 2000 BC is dedicated exclusively to women's diseases. In that document, diseases of the female genital organs are considered in conjunction with bladder diseases. Section 67 of the Ebers Papyrus, written 1500 years BC alterations regarding urination frequency, retention and "burning" is described; and the "treatment of women suffering from urine diseases and uterus." Section 24 of this same papyrus gynecological and obstetric disorders described, and contains requirements for the treatment of ulcers and inflammation of the vulva, prolapse, sterility and menorrhagia also requirements for alterations pathways urinary.